Artistic movement membership and the career profiles of Canadian painters - Douglas J. Hodgson (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2021)
Sociologists, psychologists and economists have studied many aspects of the effects on human creativity, especially that of artists, of the social setting in which creative activity takes place. In the last hundred and fifty years or so, the field of advanced creation in visual art has been heavily characterized by the existence of artistic movements, small groupings of artists having aesthetic or programmatic similarities and using the group to further their collective programme, and, one would suppose, their individual careers and creative trajectories. Certainly this is true of Canadian painting, and such movements as the Group of Seven or the Automatistes are at least as well-known to the general public as the individual artists belonging to them. We econometrically investigate the effect on career dynamics of artists as represented by the life-cycle pattern of prices obtained by their works at auction, in estimating a hedonic regression, pooled over a large sample of Canadian painters, in which variables representing the effect of a number of specific artistic groupings on the career price profiles of the members of the movements are included. Based on distinctions in the art historical and sociological literature among different categorizations of modern artistic grouping, we posit that the creativity effects of group membership can depend on the category of grouping to which an artist belongs, and distinguish between avant-garde movements and more general groupings of modern artists.
Keywords: Z11; C2; 330; art auctions; hedonic regression; creativity analysis